2018
DOI: 10.1038/s12276-018-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ras-degrading small molecules that inhibit the transformation of colorectal cancer cells independent of β-catenin signaling

Abstract: Although the development of drugs that control Ras is an emerging topic in cancer therapy, no clinically applicable drug is currently available. We have previously utilized knowledge of the Wnt/β-catenin signaling-dependent mechanism of Ras protein stability regulation to identify small molecules that inhibit the proliferation and transformation of various colorectal cancer (CRC) cells via degradation of both β-catenin and Ras. Due to the absence of Ras degradation in cells expressing a nondegradable mutant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These results suggest RAS destabilization as a pathophysiologic strategy to overcome the limitations of treating oncogenic K-RAS-driven CRC [16]. The recent identification of a small molecule that degrades RAS independently of the Wnt/β-catenin pathway and suppresses the transformation and proliferation of CRC cells harboring non-degradable β-catenin indicates the existence of an alternative way for RAS stability regulation which plays important roles in CRC tumorigenesis [18]. Direct degradation of RAS to suppress oncogenic K-RAS-mediated enhancement of CSC activation may provide a novel approach to selectively target CSCs that contribute to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest RAS destabilization as a pathophysiologic strategy to overcome the limitations of treating oncogenic K-RAS-driven CRC [16]. The recent identification of a small molecule that degrades RAS independently of the Wnt/β-catenin pathway and suppresses the transformation and proliferation of CRC cells harboring non-degradable β-catenin indicates the existence of an alternative way for RAS stability regulation which plays important roles in CRC tumorigenesis [18]. Direct degradation of RAS to suppress oncogenic K-RAS-mediated enhancement of CSC activation may provide a novel approach to selectively target CSCs that contribute to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of RAS stabilization in ISC and CSC activation has not been fully investigated. In addition to the regulation by Wnt/β-catenin signaling, a recent study revealed an alternative route to directly target RAS stability [18].…”
Section: Introductionmentioning
confidence: 99%
“…A typical HTS system, PerkinElmer's Janus Automated Workstation is widely used in industry for drug screening. [29][30][31] The Janus typically produces CVs of 3.8% using the blowout method with VersaTip Fixed Tips (PerkinElmer), dispensing 1 μL of single-fluid deionized water. 32 The CV of 4.7% using the GST is inferior to the CV of the PerkinElmer technology, but the authors are confident that with technical improvements the GST can achieve similar if not better CVs.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that both molecules cause RAS degradation, but K19 DARPins inhibit cell proliferation without interfering with wild-type KRAS cells. Moreover, Shin et al evaluated a novel RAS inhibitor, KY7749, that is able to degradate KRAS G12V in a beta-catenin-independent manner in in vitro colorectal cancer models [ 97 ].…”
Section: Therapeutic Strategies: Recent Clinical Evidencementioning
confidence: 99%